Interplay of wind-driven processes and subsurface oscillations along the leeward coastline of a tropical reef island - Arnaud Valcarcel; Joanne O’Callaghan; Joanne O’Callaghan; Mark J. A. Vermeij; Mark J. A. Vermeij (Frontiers in Marine Science)
The thermal structure of tropical reef systems is shaped by air-sea interactions, turbulent mixing, and subsurface-driven processes, yet their complex dynamics and interactions are not well understood. This study uses in situ observations and global model outputs to investigate the modulation of subsurface ocean properties by wind-driven Ekman transport, turbulent overturning, and semidiurnal temperature fluctuations, along a 70 km-long reef island coastline. Easterly trade winds prevailed for 80% of the year, during which coastal downwelling was favorable along the majority of the leeward coastline, with significant sub-island scale variability. In the surface Ekman layer, coastal downwelling and surface turbulent mixing modulated subsurface warming and mixed layer deepening. During periods of weaker winds, near-surface waters were less turbulent and buoyancy fluxes allowed for restratification. At all times, turbulence and mixing were intensified below the Ekman layer, and isopycnal depths were episodically modulated at semidiurnal frequency. On the reef, temperatures responded to Ekman transport and also varied at sub-inertial time-scales, specifically at semidiurnal frequencies. On the 60 m-deep reefs, semidiurnal temperature fluctuations drove cooling by up to 4°C. Wind and internally driven subsurface turbulence further stimulated vertical fluxes of heat and mass, relevant to local biophysical responses. This work reinforces the need to analyze the dynamic processes that regulate the subsurface biophysical structure in tropical island ecosystems.